Pelatihan Pengembangan Instrumen Asesmen Kompetensi dan Survei Karakter bagi Guru SMA Se-Provinsi Lampung - Undang Rosidin; M Setyarini; Abdurrahman; Widyastuti (Nuwo Abdimas, 2023)
The transformation in the national evaluation system from the National Examination to the Minimum Competency Assessment (MCA), has a direct impact and problem, especially for students and teachers related to adaptation and competency improvement. This community service activity aims to improve the knowledge and skills of high school teachers in Lampung Province in developing competency assessments and character surveys as the main component of MCA. The Lampung Province MKKS as partners played an important role in selecting, permitting, and following up on the results of the training activities of 45 participating teachers. The method of this activity are demonstrations, simulations, and workshops that were focused on training skills in developing competency assessment instruments and character surveys. Teachers’ improvement knowledge and skills were measured through pretest, posttest, and product assessment. The results of the analysis showed that the teachers experienced a significant increase in ability as indicated by the average normalized gain score of 0.12, the maximum score for the teacher's ability reached 85 out of 100, there were no teachers score = 0, and > 75% of teachers responded positively to the community service activities. The results of the product assessment are good categorized, which were presenting the teachers’ success in developing the instrument. These finding indicate that the training activity could be declared successful.